Evaluación de los filtros rápidos en la Planta de tratamiento de Agua Potable El Cambio que abastece a la Ciudad de Machala, Provincia de El Oro. - Zarate Reyes, Vanessa Victoria (2015)
The present work of titling proposes to carry out an assessment of the quick filters in the Drinking Water Treatment Plant El Cambio, which caters to the city of Machala to verify their efficiency within the filtering process. For this analysis was carried out physical of conductivity, pH, temperature, turbidity, total dissolved solids, dissolved oxygen, and chemical analysis of iron and manganese to groundwater from 14 existing wells in the city of Machala and water after passing by the eight existing filters fast, in the laboratory located within the treatment plant, where their results showed that the filtered water is of good quality, and is suitable for human consumption, while maintaining their values within the tolerable limit provisions by the Ecuadorian Institute of Standardization in its Technical Standard Ecuador 1108. It was also carried out a control of money laundering of the filters to determine the duration of the careers of filtration in where it was demonstrated that the flushing interval lasts between 15 to 20 hours approximately, convenient time for the elimination of sediment that may accumulate in the filters that could affect the process of the same.